Leptin as a Novel Therapeutic Target for Immune Intervention - Matarese, G.; Sanna, V.; Fontana, S.; Zappacosta, S. (Current Drug Targets - Inflammation & Allergy, 2002)
The recent cloning of the leptin (obese, ob) gene has determined fundamental insight into the understanding of the regulation of food intake, basal metabolism and reproductive function. Leptin, mainly secreted by adipocytes, belongs to the helical cytokine family and its plasma concentrations correlate with fat mass and respond to changes in energy balance. Initially, leptin was considered as an anti-obesity hormone, but experimental evidence has also shown pleiotropic effects of this molecule on hematopoiesis, angiogenesis, lymphoid organ homeostasis and T lymphocyte functions. More specifically, leptin links the pro-inflammatory T helper (Th)-1 immune response to the nutritional status and the energy balance. Indeed, decreased leptin concentrations during conditions of food deprivation lead to impaired immune capabilities. This review focuses on the potential therapeutic utilities for agents that manipulate the leptin-adipocyte axis and discusses novel strategies for an immune intervention in pathologic conditions.
Keywords: hematopoiesis